Determinansi Kebijakan Hutang pada Perusahaan Tekstil dan Garmen yang Terdaftar Di Bursa Efek Indonesia Tahun 2016 – 2020 - Ikhsan Abdullah; Arnida Wahyuni Lubis (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
This study aims to analyze what factors influence debt policy on textile and German companies listed on the Indonesia Stock Exchange for the period 2016 - 2020. The factors that influence debt policy in this study are Asset Structure, Profitability and Company Growth. This type of research is quantitative research. The population of this study amounted to 13 companies. The sample selection used purposive sampling method, so the research sample consisted of 6 companies consisting of 2016 – 2020. The data analysis method used in this study was multiple linear regression. Based on the results of the research conducted, it can be concluded that the asset structure does not have a negative effect on debt policy, profitability has a positive effect on debt policy, and company growth has a negative effect on debt policy. Simultaneously Capital Structure, Profitability and Company Growth have a positive effect on debt policy.